The Impossibility of a Virtue Ethic - Lomasky, Loren E. (Ethical theory and moral practice, 2019)
Virtue ethics is increasingly regarded as a viable alternative to consequentialist or deontological systems of normative ethics. This paper argues that there can be no such triumvirate of contending comprehensive ethical systems. That is not because virtue is unimportant but rather because genuine virtue is excellent and therefore rare. For most people in most morally salient situations there is no possibility of virtuous response because possession of the relevant virtues simply does not obtain nor can be usefully simulated. Instead, the much more universal and important moral requirement is suitable moderation of one's vices. Nor should it be supposed that the absence of virtue(s) necessarily diminishes the quality of an individual's life and that person's value to others. Rather, moral deficiencies are compatible with other excellences and may indeed contribute to them. I conclude that virtue ethics is less worthy of pursuit than vice ethics.